Genome-wide identification and validation of tomato-encoded sRNA as the cross-species antifungal factors targeting the virulence genes of Botrytis cinerea - Wu, Fangli; Huang, Yani; Jiang, Wenqin; Jin, Weibo (Frontiers in Plant Science, 2023)
Recent evidence shows that small RNAs are transferred from a species to another through cross-species transmission and exhibit biological activities in the receptor. In this study, we focused on tomato-derived sRNAs play a role of defense against Botrytis cinerea. Bioinformatics method was firstly employed to identify tomato-encoded sRNAs as the cross-species antifungal factors targeting B. cinerea genes. Then the expression levels of some identifed sRNAs were checked in B. cinerea-infected plant using qRT-PCR method. Exogenic RNA-induced gene silences analysis were performed to investigate the antifungal roles of the sRNAs, and the target genes in B. cinerea of antifungal sRNAs would be confirmed by using co-expression analysis. Results showed that a total of 21 B.cinerea-induced sRNAs with high abundance were identified as the cross-kingdom regulator candidates. Among them, three sRNAs containing a miRNA (miR396a-5p) and two siRNA (siR3 and siR14) were selected for experimental validation and bioassay analysis. qRT-PCR confirmed that all of these 3 sRNAs were induced in tomato leaves by B. cinerea infection. Correspondingly, 4 virulence genes of B. cinerea respectively targeted by these 3 sRNAs were down-regulated. Bioassay revealed that all of these 3 cross-species sRNAs could inhibit the virulence and spore gemination of B. cinerea. Correspondingly, the coding genes of B. cinerea targeted by these sRNAs were also down-regulated. Moreover, the virulence inhibition by double strand sRNA was more effective than that by single strand sRNA. The inhibition efficiency of sRNA against B. cinerea increased with the increase of its concentration. Our findings provide new evidence into the coevolution of pathogens and host plants, as well as new directions for the use of plant-derived sRNAs to control pathogens.